2016
DOI: 10.1038/cddis.2016.419
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulated microRNA by wild type and mutant p53 in induced pluripotent stem cells

Abstract: The tumour suppressor p53 plays an important role in somatic cell reprogramming. While wild-type p53 reduces reprogramming efficiency, mutant p53 exerts a gain of function activity that leads to increased reprogramming efficiency. Furthermore, induced pluripotent stem cells expressing mutant p53 lose their pluripotency in vivo and form malignant tumours when injected in mice. It is therefore of great interest to identify targets of p53 (wild type and mutant) that are responsible for this phenotype during repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 89 publications
(103 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, while reprogrammed cells with p53 deficiency formed differentiated teratomas in vivo , those with GOF mutant p53 formed undifferentiated malignant tumors, implying that it confers oncogenic properties to the reprogrammed cells ( 186 ). A few years later, Grespi et al identified a set of miRNAs whose expression altered in a p53-dependent manner during transition of mouse embryonic fibroblasts to induced pluripotent stem cells ( 187 ). The role of these miRNAs can further be investigated to determine their role in regulation of mutant p53 driven stemness.…”
Section: P53 Mutation Imparts Stem-like Properties To Cancer Cellsmentioning
confidence: 99%
“…Furthermore, while reprogrammed cells with p53 deficiency formed differentiated teratomas in vivo , those with GOF mutant p53 formed undifferentiated malignant tumors, implying that it confers oncogenic properties to the reprogrammed cells ( 186 ). A few years later, Grespi et al identified a set of miRNAs whose expression altered in a p53-dependent manner during transition of mouse embryonic fibroblasts to induced pluripotent stem cells ( 187 ). The role of these miRNAs can further be investigated to determine their role in regulation of mutant p53 driven stemness.…”
Section: P53 Mutation Imparts Stem-like Properties To Cancer Cellsmentioning
confidence: 99%
“…The result was that mutant p53 RNA expression signature was involved in the prognostic predictions in 11 different cancers [11]. Therefore, miRNAs participate in the suppression or induction of tumor development depending on the wt-or mut-p53 cell context [11,46].…”
Section: Mutant P53 and Mirnasmentioning
confidence: 99%
“…mut-p53 affects miRNA expression by inhibiting those which play a tumor-suppressing role and inducing those which have oncogenic potential [46].…”
Section: Mirnas Induced By Mutant P53mentioning
confidence: 99%
“…One of the principal negative regulators of pluripotency is the tumor suppressor protein, TP53 (Kim et al, 2011;Spike and Wahl, 2011). TP53 exerts its anti-proliferative functions mostly as a transcription factor by controlling both the expression of coding and non-coding RNAs (Lezina et al, 2013;Marouco et al, 2013;Grespi et al, 2016). p53 was shown to repress transcription of the master regulators of pluripotency, Nanog and Oct4 (Lin et al, 2005;Qin et al, 2007) (Figure 1).…”
Section: Ca 2þ Regulation Of Tp53 and Pluripotency Of Escsmentioning
confidence: 99%